Investigating the relationship between the sense of belonging to the place and the level of social security of citizens - Case study: Qom- - mohsen kameli; Hamidreza azemati (تحقیقات کاربردی علوم جغرافیایی)
Human behaviors and activities of individuals are created in urban spaces, and cultural and social relationships are formed in these spaces. Considering the main source of insecurity among citizens in the cities and the important factors such as the physical form of the city, urban structures and the shape of buildings in this case, the purpose of the study is to measure the effect of the sense of belonging to the place in increasing the level of social security of citizens City of Qom. The research method is descriptive-analytic, and the questionnaire has been used to collect the field studies. The results of the research indicate that spatial relationships and spatial arrangements in the neighborhood environment with the control and social abnormalities along with the physical and physical environment have a significant correlation. Similarly, the type of form and the size of space, which is another component of the sense of belonging to the place, has a solidarity with social abnormalities and freedom of movement. The texture and decorations of the neighborhood space have a correlation with physical and physical environment. Among them, the most correlation between dimensions of sense of belonging to place and social security is related to the freedom of movement component with the form type and space size of 0.980.